2022
DOI: 10.1021/acs.inorgchem.2c01351
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous-Phase Destruction of Nerve-Agent Simulants at Copper Single Atoms in UiO-66

Abstract: Metal−organic frameworks (MOFs) have shown great success in aqueous-phase hydrolysis of nerve agents, with some even showing promise in the gas phase. However, both aqueous-phase reactivity and gas-phase reactivity are hindered because of the binding of the hydrolyzed products to the MOF nodes in a stable, bridging configuration, which limits turnover. Single transition-metal atoms in MOFs have been a growing field of interest for catalytic applications, and single atoms have been proposed to prevent the unwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…X-ray photoelectron spectroscopy measurements on the spent catalyst further indicate the presence of both oxidation states during the reaction (Figure S6). The combination of oxidation states in Cu@UiO-66 has been recently noted via X-ray absorption spectroscopy . Additional thermal-stability studies indicate the catalyst is stable at the temperature of the experiments of this work …”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…X-ray photoelectron spectroscopy measurements on the spent catalyst further indicate the presence of both oxidation states during the reaction (Figure S6). The combination of oxidation states in Cu@UiO-66 has been recently noted via X-ray absorption spectroscopy . Additional thermal-stability studies indicate the catalyst is stable at the temperature of the experiments of this work …”
Section: Resultssupporting
confidence: 60%
“…The combination of oxidation states in Cu@UiO-66 has been recently noted via X-ray absorption spectroscopy . Additional thermal-stability studies indicate the catalyst is stable at the temperature of the experiments of this work …”
Section: Resultssupporting
confidence: 60%
“…4c). Different from the bidentate coordination of the hydrolysis product with the Zr 6 node in the hydrolysis by the pristine Zr-MOFs, this more favorable monodentate manner would greatly alleviate the product inhibition toward the catalytic activity due to the weaker Lewis acidity of Cu atoms than Zr(IV) [42,43]. The avoidance of robust product binding promotes the release of the hydrolysis product, thereby allowing for the regeneration of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Computational studies done by Snurr and Mendonca [42] indicated that modifying Zr-MOFs with Lewis acidic transition-metal single atoms may facilitate the degradation of nerve agents. Very recently, Morris' group [43] pioneered the use of SACs supported on UiO-66 for the hydrolysis of nerve agent simulants. Unfortunately, the reported SACs exhibited inferior catalytic activities to the pristine UiO-66.…”
Section: Introductionmentioning
confidence: 99%
“…Their use in Russia, England, Malaysia, and Syria, and more recent attribution as the origin of Gulf War syndrome, highlight the continued exploitation of OPAs as weapons of terror, assassination, and area denial . Recent literature reports on the interaction between OPAs and molecular transition-metal systems have lagged behind those of metal–organic framework (MOF)-based systems. While proven methods exist for effective large-scale agent destruction and surface decontamination, the current in vivo therapeutic method is decades-old and consists of a cocktail of oximes and atropine administered near their toxicity limits. The oximes act as a nucleophile to the OPA, yet their effectiveness is severely limited due to the nature of action of OPAs in the body following exposure.…”
Section: Introductionmentioning
confidence: 99%